The Role of Digital Leadership and Employee Empowerment on Employees Performance in the Manufacturing Industry in the Era of Society and Industry Revolution 5.0 - Bestadrian Prawiro Theng; Calen Calen; Nagian Toni (Politeknik APP Jakarta, 2024)
This research aims to analyze the relationship between digital leadership on employees' performance, digital leadership on organizational commitment, organizational commitment and employees' performance. Research respondents are 456 employees who work in the manufacturing industry The criteria for respondents are permanent employees, at least have worked for at least 5 years. This study is quantitative research using the Structural Equation Model (SEM) partial Least Square method, with data processing and analysis using SPSS 26 and SmartPLS 3.0 software. The majority of hypotheses developed in this research have been successfully proven, where digital leadership and employee empowerment have a direct influence on employee performance which is mediated by organizational commitment. between digital leadership and employee empowerment, organizational commitment and employee performance in the era of society 5.0.